2017
DOI: 10.11648/j.ijbecs.20170304.13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Personality Disorders and Clinical Syndromes Using the Millon Clinical Multiaxial Inventory III (MCMI-III) in an Iranian Clinical Sample

Abstract: Personality objective inventories are commonly used for diagnosis of personality disorders. Personality assessment is effective in diagnosis, prognosis and treatment of psychiatric outpatients and in patients. Comorbid personality disorders and clinical syndromes may be more worth condition of the patients. The present study aimed to examine the diagnosis of personality disorders and clinical syndromes using the Farsi version of Millon Clinical Multiaxial Inventory III (3rd ed.; MCMI-III) in Iranian psychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Also, the score of 60 is determined as the median score of psychiatric populations, and the score of 35 is determined as the median score of normal or non-psychiatric groups. Dadfar and Lester (2017) confirmed the validity and reliability of this tool in 2012 (Dadfar and Lester, 2017). In the present study, the alpha coefficient of the scales was obtained in the range of 0.82 (schizoid personality disorder) to 0.89 (narcissistic personality disorder).…”
Section: Introductionsupporting
confidence: 83%
“…Also, the score of 60 is determined as the median score of psychiatric populations, and the score of 35 is determined as the median score of normal or non-psychiatric groups. Dadfar and Lester (2017) confirmed the validity and reliability of this tool in 2012 (Dadfar and Lester, 2017). In the present study, the alpha coefficient of the scales was obtained in the range of 0.82 (schizoid personality disorder) to 0.89 (narcissistic personality disorder).…”
Section: Introductionsupporting
confidence: 83%
“…Studies have reported a prevalence of mood disorders of 9.3%, and of major depression disorder (MDD) of 8.2% 4 ; depression has been shown to be associated with suicide thoughts and attempted suicide in Iranian samples. 5,6 Many tools have been developed for depression screening, e.g. the Beck Depression Inventory (BDI),…”
Section: Introductionmentioning
confidence: 99%
“…For example, on the SCL-90 R, Ghobari Banab and Hadadi Kohsar (2010) found that paranoid thoughts were lower in Iranian females than in males students; Atef Vahid, Bolhari, Ehsanmanesh, and Karimi (2011) reported that Paranoia subscale had higher score than other subscales in general population; Habibzadeh (2014) showed that prevalence of paranoid thoughts was 46.11% among Iranian high school female students; Heidari Pahlavian, Mahjub, and Rahimi (2011) found that Iranian drug dependency obtained higher scores in Depression, Paranoid Thoughts, and Interpersonal Sensitivity subscales than nondrug dependent persons; and Fakour et al (2016) reported that the paranoia symptoms were the most prevalent disorders in patients with pemphigus (45% in female and 60% in male). On the Millon Clinical Multiaxial Inventory III (MCMI-III), Dadfar and Lester (2017) reported that one of the most common of severe syndromes was Thought Disorder (SS) (1.8%) in Iranian psychiatric outpatients, and the women patients had higher scores than men (t = 4.71, p > .000).…”
Section: Research-article20182018mentioning
confidence: 99%